Premenstrual syndrome: possibility of therapy - I A Kulikov; T V Ovsyannikova (IP Berlin A.V., 2014)
Premenstrual syndrome includes more than 200 variety of symptoms and requires more detailed examination to rule out serious medical conditions. The problem of treatment of premenstrual syndrome to be a return of women of reproductive age to normal life and work.